My favorite things : the Rodgers & Hammerstein 80th anniversary concert [videorecording (DVD)] - Reilly, David; Gattelli, Christopher; Rodgers, Richard, 1902-1979; Hammerstein, Oscar, II, 1895-1960; Lee, Simon (Conductor); Ampil, Joanna; Ball, Michael, 1962-; Friedman, Maria (MVD Visual, 2024)
Celebrate 80 years of Rodgers & Hammerstein with this landmark concert filmed at Theatre Royal Drury Lane, with songs from The Sound of Music, Carousel, South Pacific, and Oklahoma!